An IOT-enabled System for Marine Data Aquisition and Cartography - Al-Zaidi, Rabab; Woods, John; Al-Khalidi, Mohammed; Hu, Huosheng (Discoveries in Agriculture and Food Sciences, 2017)
Current satellite communication remains very expensive and impractical for most small to mid-sized vessels, and at the same time marine wireless networking is lack of network coverage. To solve this problem, this paper proposes a novel IOT (Internet of Things) enabled system for marine data acquisition and cartography based on Ship Ad-hoc Networks (SANET’s). Ships are equipped with Very High Frequency (VHF) radios and several sensors such as sea depth, temperature, wind speed and direction, etc. The collected sensory data is sent to 5G edge clouds incorporated at sink/base station nodes on shore, and ultimately aggregated at a central cloud on the internet to produce up to date cartography. The routing protocols deployed are DSDV (Destination-Sequenced Distance Vector), AODV (Ad hoc On-Demand Distance Vector), AOMDV (Ad hoc On-Demand Multipath Distance Vector) and DSR (Dynamic Source Routing) protocols, which are very popular in Mobile Ad-hoc Networks (MANET’s) and compatible with multi hop routing environments and scalability towards increased traffic and mobility. Simulation results verify the feasibility and efficiency of the proposed system that has packet delivery rates of up to 80% at shore base stations.